Factors That Affect the Accounting of Consumers to Take Advantage of Financing From Islamic Banks - Anita Wijayanti, Dimas Tri Prasetyo, Kartika Hendra & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to obtain empirical evidence on whether the factors issuingfinancial statements, application of sharia accounting, the application of loss andprofit sharing and application of accounting information systems, affect theconsumer desire to take advantage of Islamic financing, either individually orsimultaneously. In this study used a sample of 50 respondents of Bank SyariahMandiri customers Surakarta Branch. Descriptive statistical results indicate that thevariable issuance of financial statements, application of sharia accounting, theapplication of loss and profit sharing and the application of accounting informationsystem positively affect the consumer desire to take advantage of sharia financing.KeyWords : Accounting Factors, financial statements, application of sharia accounting lossand profit sharing, accounting information system, consumer desires, Syariahbank.